Penentuan Penyewa Tanah Kas Desa Potorono Menggunakan Metode Oreste dan Besson-Rank Berbasis Android - Adikka Yudha Bintang Ramadan; Tri Hastono; Nurirwan Saputra (Jurnal Dinamika Informatika, 2020)
Potorono Village is one of the villages located in Banguntapan District, Bantul Regency, DIY. Potorono Village has a total area of ​​435.46 ha. Potorono Village has several village land treasuries that can be rented by residents and certain agencies. This land lease is managed by a team of intensification of land leases in Potorono Village. The rental system has been done manually so far, so the recording and documentation is very poor. This condition is exacerbated by the determination of village treasury land tenants who are determined arbitrarily, without taking into account the agreed criteria. The transparency of the village treasury land rental is also questionable. This research provides a solution to the problem of renting village treasury land. In this study, a land rental recording system was built and the determination of village treasury land tenants was built. The method used in this research is the Oreste and Besson-Rank methods. The platform used in the research is based on Android and the programming language used is the PHP programming language. The database on the proposed system is built using MySql